Modern Strategies in the Pharmacotherapy of Inflammatory Bowel Diseases – A Literature Review - Czarnecki , Bartłomiej; Werenkowicz, Wiktor; Boral, Aleksandra; Kryś, Dominika; Brzoza, Joanna; Koczur, Julia; Górski, Michał; Pniok, Wiktoria; Kurkiewicz, Wojciech (Journal of Education, Health and Sport, 2025)
Introduction and Aim: Inflammatory bowel diseases (IBD), including Crohn’s disease and ulcerative colitis, are chronic, immune-mediated disorders of the gastrointestinal tract. Conventional therapies, such as corticosteroids, immunosuppressants, and biologics, do not consistently induce long-term remission and carry a risk of adverse events. This review aims to evaluate and compare three novel small-molecule oral agents—ozanimod, filgotinib, and upadacitinib—in terms of their mechanisms of action, clinical efficacy, and safety profiles in the treatment of IBD. Materials and Methods: This study is a literature review based on data from Phase I–III clinical trials and pharmacological analyses retrieved from PubMed and ClinicalTrials.gov. Major registration studies (e.g., TRUE NORTH, SELECTION, U-ACHIEVE) and comparative publications on long-term efficacy and safety were included. Results: Ozanimod has demonstrated efficacy in ulcerative colitis by modulating S1P1 and S1P5 receptors, with a favorable safety profile. Filgotinib, a selective JAK1 inhibitor, offers a good balance between efficacy and low thrombotic risk, particularly in biologic-naive patients. Upadacitinib shows rapid and robust clinical responses, including in treatment-refractory populations, though it requires closer safety monitoring due to potential adverse effects. Conclusions: Ozanimod, filgotinib, and upadacitinib enrich current IBD treatment strategies. Their distinct pharmacological and safety profiles enable more personalized therapeutic approaches. Further comparative studies and the development of predictive biomarkers are essential for optimizing treatment selection and improving patient outcomes.